Effect of trans-resveratrol or ubiquinol supplementation on the sperm morphology of CD-1 mice subjected to forced swimming - VAAMONDE, Δ.; SÁNCHEZ DE MEDINA, A.; CORTÉS, Β.; DÍAZ, Α.; RODRÍGUEZ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study was undertaken to assess the effect of a three-minute forced swimming protocol for 50 days, with and without antioxidant administration on sperm morphology in CD-1 mice. Seventy-five mice were randomly allocated to one of the following five groups: no exercise (control group; CG), swimming without antioxidant administration (EX), swimming with trans-resveratrol administration (EX-Resv), swimming with ubiquinol and excipient administration (Kaneka´s ubiquinol) (EX-Ubiq), and swimming with just only the excipient for Kaneka´s ubiquinol administration (EX-Excp). The EX group showed that 53.03±4.83% of sperm had abnormal morphology, with significant differences with regards to CG (46.47±10.57%) (p<0.05). The number of sperm with abnormal morphology decreased in all groups treated with either antioxidants or with excipient; this was most noticeable in EX-Ubiq (p<0.05). The percentage of midpiece and tail, as well as multiple anomalies were greater in EX than in CG (p<0.05). While both antioxidants, as well as the excipient, decreased midpiece and head anomalies, only trans-resveratrol and ubiquinol had an effect on multiple anomalies. Furthermore, only trans-resveratrol had an effect upon tail anomalies. The imposed exercise caused alterations in CD-1 mice sperm morphology, and antioxidant treatment seems suitable to decrease morphological anomalies. Both trans- resveratrol and ubiquinol were effective in decreasing simple as well as multiple sperm anomalies.